IoT-based Base Transceiver Station (BTS) Security System on Telkomsel Tower (Case Study of Telkomsel Site in Malang Area) - Oktavianto, Farel Rizky; Junus, Mochammad; Hadiwiyatno, Hadiwiyatno (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
At BTS sites, a lot of expensive telecommunications equipment is stored without adequate security. One of the telecommunication rooms that require a high level of security is the BTS (Base Station Transceiver) shelter. Nowadays crime has become part of everyday life and is difficult to separate, criminals have the opportunity to commit crimes anywhere. This research resulted in the design and manufacture of a tool that operates in the BTS battery compartment which is used to check the battery condition, how the system works, how the components work, test and analyze the system to draw a conclusion. Based on the results and testing of the IoT-based Base Transceiver Station (BTS) Security System above, several conclusions can be drawn, among others: PIR sensor test results were obtained with a delay of 5.76 seconds when sending notifications to Telegram Bot. Then in testing with RFID cards can be read properly at a distance of 1 to 5 cm by the RFID reader and when the registered card is affixed then the door lock solenoid will open, the maximum distance from the RFID reader is 5 cm. From the test results of the Infrared (PIR) sensor, the average delay is 5.76 seconds for daytime conditions with an average lux meter value of 16.2 and an average delay of 6.8 seconds at night with an average lux meter value of 0.6, this is a pretty good number because the Infrared (PIR) sensor is functioning properly.